Upaya Meningkatkan Kemampuan Mengenal Huruf Melalui Kartu Huruf Bergambar di TK Khadijah Al Kubro - Widya Nur Adha; Putri Asilestari; Citra Ayu (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research was motivated by the fact that children's letter recognition abilities at Khadijah Al-Kubro Kindergarten had not developed optimally. The problem in this research is